Pengembangan Soal Evaluasi Berbasis High Other Thinking Skills (HOTS) dan Keterampilan Berpikir Kritis pada Muatan Pelajaran Bahasa Indonesia Kelas VI SD - Bihasti, Kasrah; Muktadir, Abdul; Widi Winarni, Endang (UNIB Press, 2024)
This study aims to develop flipbook electronic teaching materials based on the group investigation cooperative model to improve students' higher-order thinking skills. The type of research used is research and development (Research & Development) 4D model (Define, Design, Development, and Disseminate). The research data was obtained through expert validation sheets and high-order thinking skills question sheets. The validated aspects include the feasibility of the material, language, and media. The validators (raters) involved to validate were six people consisting of experts and practitioners. Data on the effectiveness of the use of teaching materials were obtained from the results of the higher-order thinking skills test given to twenty-eight fifth-grade elementary school students. Based on the results of the research and development, it was concluded that flipbook electronic teaching materials based on the group investigation type cooperative model to improve students' higher-order thinking skills were very feasible and effective for learning science content on the sixth theme